The stabilization of primitive bicontinuous cubic phases with tunable swelling over a wide composition range. Issue 6 (21st November 2018) - Leung, Sherry S. W.; Leal, Cecilia
Abstract : Phase behavior of GMO/DOTAP/DOPE-PEG with bicontinuous cubic phases of different symmetry present in a wide composition range. Abstract : In this paper we investigate the pseudo-ternary phase diagram of glycerol monooleate (GMO), a cationic lipid (DOTAP – 1, 2-dioleoyl-3-trimethylammonium propane), and a "PEGylated" lipid (DOPE-PEG – 1, 2-dioleoyl- sn-glycero -3-phosphoethanolamine- N -[methoxy(polyethylene glycol)-2000 kDa]) in excess water. We use small angle X-ray scattering (SAXS) and cryogenic transmission electron microscopy (Cryo-EM) to map out a phase diagram in a regime of low DOPE-PEG content (1–5 mol%), which is pertinent for the application of lipid systems as carriers of biomolecular cargo to cells. Pure GMO is known to self-assemble into bicontinuous cubic phases of the gyroid type at low water content and of the diamond type in excess water. These complex structures have numerous advantages reaching beyond drug delivery, e.g. as protein crystallization matrices, but their formulation is challenging as very small contents of guest molecules can shift the phase behavior towards other geometries such as the lamellar phase. In this work, we show that the ternary GMO/DOTAP/DOPE-PEG system allows the stabilization of bicontinuous cubic phases in excess water over a wide composition range. The symmetry of the phase can be tuned by varying the amount of PEGylated lipid, with the primitive type dominating at low DOPE-PEG content (1–3 mol%) and the diamond phase arising at 5 mol% DOPE-PEG. In addition, we found that the diamond phase is virtually non-responsive to electrostatic swelling. In contrast, primitive bicontinuous cubic lattice dimensions swell up in equilibrium to 650 Å with increased cationic lipid content.